Replica - Black, Jenna (Tor Teen, 2013)
Sixteen-year-old Nadia lives a privileged life in the Corporate States, formerly the United States of America, but when her betrothed is killed and then wakes up in the replication tanks, the pair sets out to find a killer while keeping the secrets of human replication technology from the dangerous people who run their world.